2007
DOI: 10.1007/s11661-007-9117-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intermixed Zones of Alumina/Zirconia in Thermal Barrier Coating Systems

Abstract: The mechanisms whereby intermixed zones of alumina and zirconia are formed at the interface between the metallic bond coat and the ceramic top coat (yttria-stabilized zirconia) in thermal barrier coating systems have been investigated. The results lead to the following mechanism for the formation of the zones. The predominant mechanism for intermixed zone formation involves formation of a metastable alumina polymorph (h or c) during TBC deposition, with a significant amount of zirconia dissolved in it. The out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…However, in [23] the surface preparation before thermal barrier deposition by EB-PVD was not mentioned and the oxidation was carried out at a relatively low temperature. Our observation that Pt did not favour h-Al 2 O 3 formation is also in contradiction with the study of Stiger et al [69] where a continuous mixed zone was observed in TBC systems composed of a Ptmodified NiCoCrAlYTa bond-coating (a mixed zone is considered by many authors as being the result of the presence of transient alumina before thermal barrier deposition [69][70][71][72][73] [27].…”
Section: Pre-oxidation Study and Pt Effectcontrasting
confidence: 99%
“…However, in [23] the surface preparation before thermal barrier deposition by EB-PVD was not mentioned and the oxidation was carried out at a relatively low temperature. Our observation that Pt did not favour h-Al 2 O 3 formation is also in contradiction with the study of Stiger et al [69] where a continuous mixed zone was observed in TBC systems composed of a Ptmodified NiCoCrAlYTa bond-coating (a mixed zone is considered by many authors as being the result of the presence of transient alumina before thermal barrier deposition [69][70][71][72][73] [27].…”
Section: Pre-oxidation Study and Pt Effectcontrasting
confidence: 99%
“…Failure of the TBC coating critically depends on the characteristics of the TGO layer. If this layer is composed of a continuous, compact and adhesive alumina (Al 2 O 3 ) scale, it acts as a diffusion barrier; moreover, the alumina scale can suppress or reduce the growth of other detrimental oxides and protect the substrate from further oxidation, improving the system service life [4][5][6][7]. Many researches showed that TBC failures can be correlated to the reaching of a TGO critical thickness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…9, 10). 3 A competition between the imposed axial force and the growth strain can be also observed. In the first portion of the TGMF cycle, the applied load is less than 50 MPa, which is not enough to overcome the compressive stresses in the TGO due to the growth stresses.…”
Section: Influence Of Creep Propertiesmentioning
confidence: 93%
“…However, final spallation occurs during cooling. 3 The local trend of evolution of the TGO stresses differs slightly between the first cycle and the following cycles. This is due to that the state of stress in the system changes significantly during the first cycle.…”
Section: Influence Of Creep Propertiesmentioning
confidence: 98%
See 1 more Smart Citation